River island characteristics in Sirwan (diyala) river between Darbandikhan dam and Maydan bridge and geomorphological development (1956-2013) - صبار عبود العجيلي, عبد الله; محمد براخاص, خليل (Al-Adab Journal, 2018)
This study aims at analyzing river island characteristics in Sirwan river between Darbandikhan dam and Maydan bridge(1956-2013).The physical factors of area study and affected factor were shown in forming the islands, the formation geomorphological situation and geographical distribution of these island were also accounted with its distance and area in the mentioned period knowing its forms and geomorphological developments, so finally the effect of these river land in geomorphological applications in Sirwan river in the some area and region growth.